Uncertain merger synergies, passive partial ownership, and merger control - Shiva Shekhar; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
We examine the competitive effects of a passive partial ownership (PPO) when it serves as an instrument for the acquirer firm to learn the merger synergies with the target firm in advance. The realization of a synergy is uncertain ex ante, so that a direct merger exhibits a downside risk not only for the merging candidates but also for consumers. We show that minority shareholdings can reduce this downside risk as they allow for a sequential takeover where the acquirer takes an initial minority share, becomes an insider, and learns the merger synergy. We show how this feature of PPOs affects a firm's takeover strategy and the decision problem of the antitrust authority. We derive implications for a merger control approach to PPO acquisitions, where we examine a forward looking price test and a safeharbor rule.
Keywords: L13; L41; 330; Merger Control; Passive Partial Ownership; Synergies